Análise da eficácia do uso de acelerômetro para monitorar os movimentos do corpo durante exercícios em equipamentos ao ar livre - Bednarski, Fernando (2024)
Physical inactivity is a major public health problem, as it has a direct impact on the generation and increase in cases of illness in the private and public spheres, and consequently on the increase in public spending. In this respect, in order to help prevent and reduce sedentary lifestyles, governments around the world have taken various actions, one of which is to set up outdoor gyms. However, despite the importance of these projects, specialized and qualified professionals are not available in these places to guide the proper use of the various devices and, in this scenario, exercises performed incorrectly can have harmful effects on the individuals who perform them. The aim of this study was to monitor and analyze the biomechanical profile of the movements of the body segments of healthy subjects while exercising on Outdoor fitness equipment (OFE). To do this, the accelerometer and the computer application Sistema de Monitoramento de Movimentos e Análise Remota em Telemedicina (SMMAR-T) with sound alert were used to collect and analyze the biomechanical data, both devices being present and installed on the smartphone respectively. Twelve healthy individuals were divided into three groups with four subjects each: Groups 1 (G1), 2 (G2) and 3 (G3), represented by individuals aged 18 to 25, 30 to 40 and 50 to 60, respectively. The absence of injuries or illnesses in the participants is determined by a written declaration by the subject and confirmed by semi-technical procedures carried out by the physiotherapist researcher. After these procedures, the biomechanical data of the movements of the body segments performed during the exercises in the selected OFE was collected. First, each individual performed movements of 100% range of motion for each OFE chosen by the professional. This was done by calculating two situations, that is 20% and 70% displacement from the integral movement of 100%. Once these angular values had been determined, each subject performed three sets of 10 repetition cycles for each type of apparatus, with the presence of sound to alert them when they had reached the displacement desired by the professional specialist and without the presence of sound. After these processes, these attributes captured by the application were compiled to determine Acceleration versus Time graphs and, automatically by the application, for Displacement versus Time, and the physical quantities such as speed, displacement, precision and accuracy of the displacements were analyzed. The SMMAR-T application was used to determine, monitor and analyze the normality of the characteristic movements of each ApAAls performed by the healthy individuals, as well as the effectiveness achieved when comparing the movements with and without sound alerts of the body movements requested by the health specialist. Through analysis, the sound alerts increased the effectiveness and precision of the desired movements. With this, it is believed that the exercises proposed by the health professional can be practiced with greater effectiveness and safety.